Risk Management of Sovereign Assets and Liabilities - Cassard, Marcel (IMF Working Papers; Working Paper ;, 1997)
In an environment of sizable and volatile capital flows and integrated international capital markets, large and unhedged net external sovereign liabilities expose countries to swings in international asset prices and to potential speculative currency attacks. The paper argues that an essential step in reducing emerging market vulnerability to such external shocks is to reform the institutional arrangements governing asset and liability management policies, so as to promote a transparent, publicly accountable, and professional incentive structure.